2020
DOI: 10.3390/jrfm13100226
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of the Volatility Spillover Effect between World-Leading and the Asian Stock Markets: Implications for Portfolio Management

Abstract: This study employs the Vector Autoregressive-Generalized Autoregressive Conditional Heteroskedasticity (VAR-AGARCH) model to examine both return and volatility spillovers from the USA (developed) and China (Emerging) towards eight emerging Asian stock markets during the full sample period, the US financial crisis, and the Chinese Stock market crash. We also calculate the optimal weights and hedge ratios for the stock portfolios. Our results reveal that both return and volatility transmissions vary across the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Discussing regional market integration within the Indian subcontinent and the implications of these on the BSE Oil and gas sector as compared to the rest of sectors could prove to be an interesting line of research. Yousaf, Ali & Wong (2020), Volatility Spillovers between World Leading and Asian Stock Markets: An Empirical Analysis [11]. The study provides a glimpse of how global market dynamics impact the local and regional markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Discussing regional market integration within the Indian subcontinent and the implications of these on the BSE Oil and gas sector as compared to the rest of sectors could prove to be an interesting line of research. Yousaf, Ali & Wong (2020), Volatility Spillovers between World Leading and Asian Stock Markets: An Empirical Analysis [11]. The study provides a glimpse of how global market dynamics impact the local and regional markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, no such pattern emerged during the Chinese stock market crash. This implies that, during the Chinese stock market downturn, portfolio investors in Asian stock markets could enhance diversification benefits by including Chinese stocks in their portfolios [5]. Risk measurement is particularly important in the current financial market environment due to world uncertainties, environmental issues, and demographic issues.…”
Section: Risk Measurementmentioning
confidence: 99%
“…The evidence also suggested that the differences between the turbulent and calm periods do exist. Based on the VARasymmetric GARCH model, Yousaf et al (2020) observed stock return spillover from the US and China to the Asian stock markets during the US financial crisis and the Chinese stock market crash, and the volatility was transmitted from the US to the majority of the Asian stock markets during the Chinese stock market crash. Additionally, volatility was transmitted from China to the majority of the Asian stock markets during the US financial crisis.…”
Section: Review Of Extant Literaturementioning
confidence: 99%